NEP 2020 and the Rise of Holistic Education: A Comparative Study with Global Education Models - Kumar, S. Chetan (AG Volumes, 2025)
Education is the primary source of morals and values in pupils, and a strong educational system is crucial to a country’s progress. Between the Vedic and contemporary eras, the Indian educational system has advanced significantly. Its dynamic nature is the most valued aspect of any system. India adopted the New Education Policy, 2020 in response to this viewpoint. This research centres on a comparative analysis of the global education model and NEP 2020. An analysis of NEP 2020 in relation to international education models from Finland, the United States, and Germany demonstrates India’s attempts to conform to global best practices. It comes to the conclusion that the Finland educational system is flexible as comparable to NEP 2020 in that both emphasise student-centered learning and holistic methods. The US educational system is also reflected in NEP 2020, which supports India’s progress towards international educational competitiveness. Despite its historical emphasis on STEM courses and rote learning, India’s educational system is beset by issues including inadequate facilities, poor teacher pay, and a lack of practical training. On the other hand, Germany’s approach of vocational and practical training provides insightful information.